Theoretical and Experimental Verification of Organic Granular Fertilizer Spreading - Vaidas Bivainis; Eglė Jotautienė; Kristina Lekavičienė; Ramūnas Mieldažys; Gražvydas Juodišius (Agriculture, 2023)
Due to the continuous creation of organic granular fertilizers of the new composition, there is a lack of knowledge about their properties and the influence of the norm on spreading efficiency. To increase the efficiency of the use of granular organic fertilizers, their spreading aims are to properly choose the most rational spreading parameters and fertilizer norms, considering the characteristics of the fertilizer. To determine this quickly and with lower costs, various theoretical models and computer programs are used to study the dynamics of fertilizer spreading. The purpose of this work was to perform theoretical and experimental comparative studies of the influence of the characteristics and dosage norms of granular fertilizers of poultry manure on the spreading efficiency. During the research, the physical properties of granular poultry manure fertilizers were determined, which have an impact on the quality of spreading. Experimental studies of fertilizer spreading were carried out using two centrifugal spreaders with the same parameters (Amazone ZA-M-1001 (spreading dosage norm, 200 kg ha−1 and 400 kg ha−1; driving speed, 10 km h−1) and ZA-M-1201 (spreading dosage norm, 600 kg ha−1, 800 kg ha−1, and 1000 kg ha−1; driving speed, 5 km h−1)). Before the fertilizer was spread, measurements were made of the flow rate of the spreadable fertilizer through one bunker shutter. Fertilizer application simulations were performed using the discrete element simulation program EDEM. Research has shown that spreading the studied granular fertilizers at the dosage norm of 600 and 800 kg ha−1 allows for the future expansion of the limits of spreading research using a spreading simulation. The most important directions of research would be the research of the spreader vanes’ shape, length, and rational settings positions, using the standard commonly used centrifugal spreader, after making small modifications of the spreader, to achieve that the spreader could spread larger norms of fertilizer or drive faster during spreading.